Rekonstruksi Regulasi Kewenangan Dewan Perwakilan Rakyat dalam Pemilihan Pejabat Publik pada Komisi Negara Independen - Rofiqul Umam Ahmad (Jurnal Identitas, 2024)
The authority of the Indonesian House of Representatives (DPR RI) in appointing public officials to independent state commissions is fraught with challenges, including the oligarchic dominance of political parties, the subordination of objectivity to political interests, weak mechanisms for assessing candidates’ capacities, and the potential for negotiation and transactional practices during the selection process. This study employs an empirical juridical approach within the framework of constructivist paradigm, combining normative and sociological legal analyses. Findings reveal systemic weaknesses not only in the regulatory framework but also in the conduct of key actors—both DPR members and prospective officials—as well as within the institutional structure of independent commissions and the system of checks and balances between the DPR and the President. This article aims to describe, critique, and reconstruct DPR’s regulatory authority through the cases of the Corruption Eradication Commission-KPK, the General Elections Commission-KPU, and the National Human Rights Commission-Komnas HAM. Regulatory reconstruction is deemed essential to strengthen institutional independence, prevent political interference, and ensure transparent, accountable public official appointments that uphold the quality and integrity of independent state bodies.